Pembuatan Game Tradisional Dakon Multiplayer Menggunakan Java - Utami, Reny; Purnama, Bambang Eka; ., Sukadi (Speed - Indonesian Journal on Computer Science, 2014)
Abstract : A variety of traditional games should be maintained and preserved as national heritage. But in todays traditional games started ignored by the technology game. One of the traditional game that is quite popular is dakon. Dakon game known as Javanese traditional game though the game is also known in other areas. Games dakon probably considered old-fashioned, outdated. This game is actually a tiny flake of blocks of culture and character of the nation in which we can actually reap the many benefits that sometimes we do not realize it. Based on the description author will  make a traditional game dakon multiplayer using java , which is an effort to preserve traditional games that culture is not forgotten by the children in spite of the development of increasingly sophisticated technology. Keywords: Dakon, Traditional Game Abstraksi : Permainan tradisional yang beragam  seharusnya dipertahankan dan dilestarikan sebagai  warisan  budaya  bangsa.  Namun  pada  jaman  sekarang  ini  permainan tradisional mulai terabaikan dengan adanya permainan berteknologi canggih. Salah satu permainan  tradisional  yang  cukup  populer  adalah  dakon. Permainan dakon dikenal  sebagai permainan tradisional masyarakat Jawa sekalipun permainan ini dikenal juga di daerah lain.   Permainan  dakon  barangkali  dianggap  telah  kuno,  ketinggalan  jaman. Permainan  ini sesungguhnya merupakan serpihan kecil dari unsur pembentuk budaya dan karakter bangsa  dimana  sesungguhnya  kita  bisa  memetik  banyak manfaat  yang  kadang  kita sendiri  tidak  menyadarinya. Berdasarkan uraian tersebut penulis akan membuat sebuah game tradisional dakon multiplayer menggunakan java, yang merupakan suatu upaya  mempertahankan  permainan tradisional  agar  budaya  bangsa  tidak  terlupakan  oleh  anak-anak  meskipun    adanya perkembangan teknologi yang semakin canggih.   Kata Kunci      : Dakon, Game Tradisional